2008
DOI: 10.1103/physrevlett.100.233902
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Induced Motion Control of Drifting Solitary Structures in a Nonlinear Optical Single Feedback Experiment

Abstract: We realize an absolute position control of drifting dissipative optical solitons by injecting an incoherent amplitude parameter gradient onto the nonlinear optical system. This allows for two-dimensional, arbitrary control patterns. The control of the soliton drift velocity is studied applying a periodic, hexagonally shaped modulation. The guiding of dissipative solitons by one- and two-dimensional parameter modulations is demonstrated. Furthermore, one-dimensional, line-shaped parameter modulations are design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Quantitative investigations on SDS drift were recently performed in a LCLV (Gütlich et al (2007); Cleff et al (2008)). It was confirmed that the speed of the SDS is proportional to the strength of the imposed phase gradient as expected from Eq.…”
Section: Exploring the Mobility Of Sdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative investigations on SDS drift were recently performed in a LCLV (Gütlich et al (2007); Cleff et al (2008)). It was confirmed that the speed of the SDS is proportional to the strength of the imposed phase gradient as expected from Eq.…”
Section: Exploring the Mobility Of Sdsmentioning
confidence: 99%
“…(4), at least on "average". The erratic deviations from the expected ideal behavior in speed and direction of drift are due to background gradients related to imperfections of the device (Gütlich et al (2007);Cleff et al (2008)). A modulation in SDS speed can be induced by superimposing a modulation onto a gradient.…”
Section: Exploring the Mobility Of Sdsmentioning
confidence: 99%
“…In the study of the nonlinear optical systems, Ref. [32] exhibited the experimental control of drifting solitary structures and their motions by using an incoherent external amplitude control in a unique way. And the drifting solitons can be explained in this paper by the shape changes of the soliton solutions with time, such as dromion excitation (Fig.…”
Section: IV Iv Iv C C C Conclusion Onclusions Onclusions Onclmentioning
confidence: 99%
“…The interplay of localized states with a structured background is particularly interesting in nonlinear optics, where it opens interesting technical issues on the control of localized structures, with the possibility of driving their dynamics and tailoring their interactions [25][26][27][28]. Here, we present a general description of bi-pattern systems, by which we mean systems that exhibit coexistence between two distinct pattern states and are, therefore, able to generate localized peaks.…”
Section: Introductionmentioning
confidence: 99%